Проблема існування розв’язку в задачах розподілу потоків - Kirik, O. E. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
Questions of the existence of a solution for the problem of flow distribution in power networks are investigated. The algorithm of a priori definition of restrictions compatibility of this problem is formulated. A model with the system of equations of continuity, built in such a way as to ensure the existence of a feasible solution provided to minimize disruption customer orders is constructed.